2020
DOI: 10.1016/j.jhin.2020.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with preventive behaviours of COVID-19 among hospital staff in Iran in 2020: an application of the Protection Motivation Theory

Abstract: This study was conducted to predict the preventive behaviours of healthcare workers (HCWs) towards COVID-19 based on the Protection Motivation Theory (PMT). This crosssectional and analytical study was conducted on 761 HCWs in Hamadan, Iran, using multi-stage random sampling. The preventive behaviours against COVID-19 among HCWs were assessed at a relatively desirable level. Based on the PMT, threat and coping appraisal were predictors of protection motivation to conduct COVID-19 preventive behaviours (P<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
159
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(219 citation statements)
references
References 7 publications
33
159
6
3
Order By: Relevance
“…Stated differently, our findings suggest that individuals who perceive themselves as able to carry out (i.e., those with self-efficacy) those behaviors judged as effective in reducing the threat (i.e., behaviors with perceived efficacy) are more likely to comply with the government measures. This finding highlights the key role of self-efficacy in the adoption and maintenance of recommended health actions [ 21 ] and suggests a relationship between self-efficacy and compliance with the preventive measures during the COVID-19 pandemic, as previously reported for different populations (e.g., healthcare workers) [ 68 , 69 ]. Furthermore, some covariates were also significant: older age, lower education levels, and lower levels of personality dysfunction were all associated with increased compliance.…”
Section: Discussionsupporting
confidence: 78%
“…Stated differently, our findings suggest that individuals who perceive themselves as able to carry out (i.e., those with self-efficacy) those behaviors judged as effective in reducing the threat (i.e., behaviors with perceived efficacy) are more likely to comply with the government measures. This finding highlights the key role of self-efficacy in the adoption and maintenance of recommended health actions [ 21 ] and suggests a relationship between self-efficacy and compliance with the preventive measures during the COVID-19 pandemic, as previously reported for different populations (e.g., healthcare workers) [ 68 , 69 ]. Furthermore, some covariates were also significant: older age, lower education levels, and lower levels of personality dysfunction were all associated with increased compliance.…”
Section: Discussionsupporting
confidence: 78%
“…In the present research, protective behaviors showed to be at a desirable level, which is consistent with some research by Barati et al about protective behaviors among hospital staff (34). Moreover, in the present research among preventive behaviors, avoiding unnecessary travel was found to be the most prevalent protective behavior, which seems to result from limits set by social distancing.…”
Section: Resultssupporting
confidence: 92%
“…A statistically signi cant positive correlation was also observed between perceived vulnerability and severity of the disease. This nding is consistent with a number of studies including Barati et al (34)., Zare et al (21) and Park et al (35). These ndings show that for a better perception of the risk of a iction with the disease, a higher level of perceived vulnerability is needed, as such a perception can strongly and positively affect the perceived threat of COVID-19.…”
Section: Resultssupporting
confidence: 90%
“…In the present research, protective behaviors showed to be at a desirable level, which is consistent with some research by Barati et al about COVID-19 protective behaviors among hospital staff (34). Moreover, in the present research among preventive behaviors, avoiding unnecessary travel was found to be the most prevalent protective behavior, which seems to result from limits set by social distancing.…”
Section: Discussionsupporting
confidence: 91%